Comparison of spectroscopic and dynamical mechanical characteristics of some polymer composites on polypropylene base - Mamedov, SV; Alekperov, VA; Lenger, Y; Ören, D; Abasov, SA; Subasi, M; Bayramova, RL (SOC PLASTICS ENG INC, 1999)
In this study the mutual investigation of the results obtained from the mechanical stability properties and the IR spectra of polypropylene-based but differently doped low-density polyethylene (LDPE) and o-o-di-n-cresylditio phosphorous (CTPh) acid polymer composites is given. As opposed to the studies of the writers in recent years here, dynamical-mechanical properties are explained not only by the variations in the oxidation peaks but also by the optical density in the peaks of the variations in the groups in amorphous and crystalline regions. The properties are also explained by the spectra variations in the IR region, which, according to Mamedov (2), is important, and by the extreme variations of the polymer properties. IR spectra analyses show that for both composites, 1) the optical density of the peaks in the crystalline regions for LDPE decreases while for PP those of the peaks in the amorphous regions increase; 2) the optical density of the peaks belonging to the C=C groups get higher, whereas those of the peaks 1717, 1748 cm(-1) diminish; and 3) the dynamical-mechanical properties change accordingly, and these changed composites have the maximal characteristics, since the added amount is 0.2-0.3% CTPh by mass and 20-30%LDPE by mass. On the basis of the paper by Abdullayev et at (3), the mechanism of these processes is given.
Keywords: Materials Science; Polymer Science